Effectiveness of Counseling onthe Willingness to Use Intra-Uterine Device Contraceptive After Placenta Detachmentamong the Health Insurance Participants in Panembahan Hospital, Bantul - Ristiana Eka Ariningtyas; Hermanu Joebagio; Eti Poncorini P (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Counseling on family planning and contraceptive use after deliverymay increase awareness of women to use contraceptives. Any use of contraceptives there are side effects, including in the use of contraceptives used in the uterus post placenta, side effects and failure was a factor that caused the acceptors are having dropped out of the methods used. This study aimed to determine the effectiveness of counseling on willingness to use intra-uterine device contraceptive after delivery.Subject and Methods: This was a qualitative study with case studies carried out in Bantul Yogyakarta. A total of 3 midwives and 3 contraceptive use in the uterus post placenta acceptor Panembahan Senopati hospital. The dependent variable was health insurance participant. The independent was contraceptive used in the uterus post placenta. The data collected by interview, observation, document. The informant was 3midwifery and 3 acceptor of post placenta.Results: Socialization and counseling is done always accompanied and informed consent when the pregnancy inspection. Midwives play a role in counseling process by involving the husband as support for potential acceptors. Such side effects are still within the limits of reasonable expulse. Contraceptives used in the uterus post placentainstallation carried out by a competent midwife by SPO. Midwives provide education and counseling reset when the client still complained of side effects.Conclusion: Socialization and counseling potential acceptors are effective to increase willingness to use intra-uterine device contraceptive among the health insurance participants.Keywords: counseling, intra-uterine device contraceptiveCorrespondence: Ristiana Eka Ariningtyas. STIKes Jenderal Ahmad Yani, Yogyakarta. Email: tyasarin1988@gmail.com. Mobile: 08985069979.Journal of Health Policy and Management (2016), 1(1): 8-12https://doi.org/10.26911/thejhpm.2016.01.01.02